Ideal disciples: a commentary on Matthew's Beatitudes - Daley, Daniel (Baylor University Press, 2024)
"A theological exegesis of the Beatitudes from the Sermon on the Mount for a practical, ethical roadmap of the Christian life as emulation of the pattern of Jesus"--